Verbal overabundance in the Italian grammatical tradition: the evolution of ferire, languire, patire, perire, and tradire - Grochowska-Reiter, Anna (Kwartalnik Neofilologiczny, 2026)
The article, based on a corpus oof 125 grammars and manuals for native speakers and foreign learners (16th–21st centuries), reconstructs verbal overabundance in the verbs ferire, languire, patire, perire, and tradire. In sixteenth-century sources, infixed and non-infixed variants are functionally distributed (common usage vs poetic register). From the 17th century onward, descriptions become more selective; between the 18th and 19th centuries, the norm increasingly labels non-infixed forms as poetic or archaic, until their exclusion from the standard.